expression OF MODALITY AND EVALUATION IN HILLARY CLINTON'S SPEECH - Aisyah, Santi Siti (2012)
The study entitled "expression of Modality and Evaluation in Hillary Clinton's Speech" aims to find out the types of modality and evaluation that were used by Clinton and to identify how the use of modality and evaluation reveals the speakers' commitment toward human rights of Lesbian, Gay, Bisexual and Transgender (LGBT) people. The study is qualitative with textual analysis approach. However, some descriptive quantitative is also conducted. Halliday's Systemic Functional Linguistic is the tool analysis in this study. The result shows that the modality occurs in terms of epistemic and deontic. Moreover, the evaluation occurs in terms of desirable and undesirable. The occurrence of epistemic and deontic modality in speech shows Clinton's commitment. Meanwhile, in terms of desirable and undesirable, the occurrence of Assumed Value shows that Clinton tends to deliver her thought implicitly.